Perbandingan Kontribusi Pajak Hotel Dan Restoran Terhadap Pendapatan Asli Daerah Masa Pandemi Covid-19 Dan New Normal - Hemas Noor Fadilla; Novi Lailiyul Wafiroh (LPPM ISNJ Bengkalis, 2022)
The covid-19 pandemic has impacted Indonesia's economic sector, including local revenue from taxes. This study compares the growth rate and contribution of hotel and restaurant taxes to Jombang Regency's original revenue during the covid-19 pandemic and the new normal. This research is a descriptive study using a quantitative approach. The source of data used is secondary data in the form of documentation. Data analysis using growth rate and contribution analysis. This study shows that the growth rate of hotel and restaurant tax revenues during the covid-19 pandemic and the new normal both increased. The contribution of hotel and restaurant taxes to original regional income during the covid-19 pandemic and the new normal increased but was included in the deficient category. This research can complement existing theories, become a reference for taxpayers to be obedient in paying taxes and become a reference for the Jombang district government to increase local tax revenues.